Molecular epidemiology and clinical features of Hepatitis C Virus (HCV) in epidemic areas of Interior Sindh, Pakistan - Bhatti, Shameem (Pak J Med Sci, 2016)
OBJECTIVE: Highly variable genome of HCV and high prevalence in many geographical areas made it necessary to conduct local population studies. This study has been conducted to show HCV parameters along with clinical features in the local population of interior Sindh, province of Pakistan. METHODS: Present study was conducted in from August 2010 to November 2015 in the rural areas of Sindh, Pakistan. All the 31560 screened samples selected for the study were tested by second Generation Enzyme Linked Immunosorbent Assay (ELISA Biokit 480&96). RESULTS: Total 31560 people were screened for HCV and out of these 13.67% (n= 4314) HCV infected patients. When 4314 samples of patients were examined; the anti-HCV was significantly higher in males 2814 (14.98%) than in females 1500 (11.74%) with P value = 0.06. The age of the patients ranged from 18 to 65 years. Out of 4314 HCV samples, 3020 (70%) were of Genotype 3a, 237(5.5%) of Genotype 2a, 108 (2.5%) of Genotype- 1a, 216 (5%) of Genotype 1b, 237 (5.5%) of Genotype 3b and 43 (1%) of Genotype 4. Additionally, 108 (2.5%) had co-infection and 345 (8%) samples showed no result –designated as untypable by the genotyping. CONCLUSION: This study showed that HCV is most frequently reported disease with genotype 3a being the most prevalent genotype.